Dispersion measure variations in pulsar observations with LOFAR - Ibrahim, Abubakr (Department of Astronomy, 2020)
I present an analysis of the dispersion measure (DM) variations for 68 pulsars. The observations were taken using six International LOFAR Stations in Europe over the period of 3.5 years (between June 2014 and November 2017) at the centre frequency of 150 MHz with 80 MHz of bandwidth. During this time each pulsar was observed on weekly basis resulting in an average of 160 observations per source. I show that, the variations of the DM measurements show various trends along the span of the observation: increasing or decreasing, and in some cases more changes from one trend to another. I perform the structure function analysis for each of observed pulsar included in the study, in order to check if the DM variations follow the Kolmogorov power spectrum which describes the turbulence structure of the interstellar medium (ISM). I find that for a number of pulsars results show consistency with the Kolmogorov distribution (e.g. PSRs J1913−0440 and J2157+4017) while other sources show significant difference (e.g. PSRs J0108+6608 and J0614+2229). I also obtain the DM derivatives (i.e. dDM/dt) for each pulsar, in order to examine the correlation between the DM and its derivative. The result of this correlation shows a best-fit with a square-root dependence of 0.6±0.2, which is comparable with the result that was previously obtained by Hobbs et al. (2004), who shows a dependence of square-root between the DM and its derivative; with a gradient of 0.57±0.09. Also, one of the major results of this study that, thanks to the timing analysis, allowed me to produce a new timing solution for three pulsars: PSRs J0613+3731, J0815+4611 and J1740+27. This study concludes in that: i) the DM variations can be used to understand the general properties of the ISM ii) the low-frequency observations can enable us to study the dispersion effect on pulsar signals, which can be very useful for the effort of the pulsar timing array (PTA) project iii) IISM studies using pulsar timing is a powerful technique requiring careful approach to data reduction and analysis due to characteristic of the pulsars.